Audit of Otological Diseases amongst Elderly in Nigeria - Kayode, Aremu Shuaib; Alabi, Biodun Sulymam; Segun, Segun-Busari; Ogah, Stephen A. (Arquivos Internacionais de Otorrinolaringologia, 2010)
Introduction: Aging process is associated with degeneration in different part of the body There is scarcity of literature on the otological diseases in the elderly black African especially Nigerian which is the largest African nation. Thus this study is done with the aim of highlighting the pattern of otological diseases in elderly for careful cost-effective health care plans and to make the aging period more fulfilling and tolerable to the elderly. It is therefore hope that the information will go a long way to assist other African countries as well.Method: The study is a ten year hospital-based retrospective study between January, 1999 and December, 2008 at the ENT Department of Unilorin Teaching Hospital Ilorin. All patients aged 65 years and above with otological complaints were included in the study.Results: A total of 740 Elderly patients were included in the study. The male to female sex ratio was 1.5:1.0.Petty Traders accounted for 300 (40.5%) of cases; 87 (11.8%) were Farmers; 250 (33.8%) were Retired Civil Servants; 68 (9.2%) were Unskilled Laborers and 35 (4.7%) were full-time Housewives. Aural wax impaction was the commonest otological disease found, accounting for 360 (48.7%) of cases, Hearing loss (presbyacusis),158 (21.4%); Tinnitus,78 (10.5%) and Otomycosis,64 (8.5%).Other conditions were CSOM,34 (4.6%);Foreign body Impaction,32 (4.3%); Vertigo,10 (1.4%) and Aural Tumours,5 (0.6% ).Conclusion: Aural wax impaction was the commonest disease found, thus it is important to always do full audiologic evaluation after aural syringing to rule out other conditions such as presbyacusis and aural tumours in elderly. Continuing medical education is recommended for the general practitioners for early recognition and referral.
Keywords: ear diseases; aged; otitis media; suppurative